Outcomes of Adjuvant Radiotherapy Following Negative Surgical Margins for Cutaneous Squamous Cell Carcinoma. Issue 9 (September 2019) - Miller, Jonathan; Chang, Timothy; Schwartz, David; Peters, Margot; Baum, Christian
Abstract : BACKGROUND: The role of adjuvant radiotherapy (ART) for cutaneous squamous cell carcinoma (cSCC) following negative surgical margins is unclear. OBJECTIVE: To retrospectively examine the clinical outcomes in a cohort of patients with cSCC who completed ART after Mohs micrographic surgery or wide local excision with negative margins. METHODS AND MATERIALS: After the institutional review board approval, a retrospective review was conducted of all patients with cSCC treated in the Mayo Clinic Department of Radiation Oncology from March 10, 1998, through April 26, 2013. Inclusion criteria were age >18 years, resection with negative histologic surgical margins, and completion of ART. RESULTS: Thirty-two patients met the inclusion criteria: 15 patients died, 12 without evidence of disease related to cSCC. Three patients developed recurrent disease, all with poorly differentiated cSCC, > 2 cm in clinical diameter, perineural invasion, and Brigham and Women's (BWH) stage T2b/T3; 2 of 3 patients were immunosuppressed; and 2 of 3 patients died of cSCC-related causes. CONCLUSION: These data suggest that the combination of surgical resection and ART is a reasonable option for Brigham and Women's T2b/T3 tumors.